Schooling Data, Technological Diffusion, and the Neoclassical Model - de la Fuente, Angel; Doménech, Rafael (American Economic Review, 2001)
Growth economists have spent more than forty years slowing chipping away at the Solow residual, largely by attributing increasingly larger chunks of it to investment in human capital. A few years ago we were reasonably certain that this was the way to go. But an increasing number of studies seem to be telling us that the effect of schooling variables on productivity vanishes when we turn to what seem to be the appropriate econometric techniques for the purpose of estimating growth equations. Should we take these results at face value? Before we do so and abandon the only workable models we have, it seems sensible to search for ways to reconcile recent empirical findings with some kind of plausible theory. In this paper we argue that we can make a fair amount of progress in this direction by combining two ingredients: better data on human capital, and a further extension of the human capital-augmented neoclassical model that allows for cross-country productivity differentials and for technological diffusion.